2020
DOI: 10.1002/asl.973
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanisms of summer Korean heat waves simulated in a long‐term unforced Community Climate System Model version 3

Abstract: We investigate the natural variability of summer Korean heat waves through a long‐term (500 year) unforced simulation using the Community Climate System Model version 3. A total of 82 extreme heat wave frequency (HWF) years are identified with positive barotropic geopotential height (GPH) anomalies over the Korean Peninsula. These anomalies represent the most important atmospheric pattern that causes Korean heat waves via adiabatic warming by anomalous subsidence. From a composite analysis of the extreme Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…1b and Fig. 2b) is specifically important in terms of the interannual variabilities in TMAX and NHD, which is consistent with the Pacific-Japan (PJ) teleconnection (Nitta, 1987) and previous studies (Kosaka and Nakamura, 2006;Lee & Lee, 2016;Yeh et al, 2018;Yeo et al, 2019;Kim et al, 2019;Kim et al, 2020), indicating that the OLR over the region can be one of diagnostic indices explaining heatwaves in Korea Notably, another strong convective activity related to heatwaves in Korea is located over northwestern India ( Fig. 1b and Fig.…”
Section: Heatwave In Korea and Associated Diagnostic Indicessupporting
confidence: 89%
“…1b and Fig. 2b) is specifically important in terms of the interannual variabilities in TMAX and NHD, which is consistent with the Pacific-Japan (PJ) teleconnection (Nitta, 1987) and previous studies (Kosaka and Nakamura, 2006;Lee & Lee, 2016;Yeh et al, 2018;Yeo et al, 2019;Kim et al, 2019;Kim et al, 2020), indicating that the OLR over the region can be one of diagnostic indices explaining heatwaves in Korea Notably, another strong convective activity related to heatwaves in Korea is located over northwestern India ( Fig. 1b and Fig.…”
Section: Heatwave In Korea and Associated Diagnostic Indicessupporting
confidence: 89%
“…Extended high pressure over the Korean Peninsula is considered to be the large-scale atmospheric condition responsible for heat waves in the Korean Peninsula (Yeo et al 2019;Kim et al 2018;Lee et al 2020a;Kim et al 2019Kim et al , 2020. Yeo et al (2019) analyzed long-term heat wave cases from 1979 to 2017, and identified two types of heat waves caused by high pressure: a zonal wave type with high pressure originating in Europe and reaching East Asia after passing through Eurasia, and a meridional type with high pressure induced in East Asia due to convective activities in the western Pacific subtropical region.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have emphasized the importance of the dynamic effects that induce EHDs 5 , 12 , 14 , 18 22 . Dynamically, a persistently positive geopotential height (GPH) anomaly is accepted as the most important atmospheric factor leading to the occurrence of EHDs because it provides favorable conditions for EHDs via adiabatic warming caused by downward motion 20 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have emphasized the importance of the dynamic effects that induce EHDs 5 , 12 , 14 , 18 22 . Dynamically, a persistently positive geopotential height (GPH) anomaly is accepted as the most important atmospheric factor leading to the occurrence of EHDs because it provides favorable conditions for EHDs via adiabatic warming caused by downward motion 20 , 22 , 23 . Focusing on the Korean Peninsula, EHD-related atmospheric circulation patterns are intimately associated with two types of wave trains generated by enhanced convection over the subtropical western North Pacific (WNP) 5 , 14 , 18 , 20 , 22 and mid-latitude Northern Hemisphere wave dynamics 14 , 19 , 20 22 .…”
Section: Introductionmentioning
confidence: 99%